Menelisik Strategi Pemasaran Rumah Sakit Menggunakan Market Based-Management - Noveri Maulana (Universitas Pendidikan Nasional, 2020)
ABSTRACTThis research is aimed to develop a strategic marketing plan for a Heart & Cardiovascular Hospital in Jakarta coded Hospital XYZ. The strategic framework in this study is using market-based management concept which is rarely used in the healthcare business development. Mix method analysis are implemented in this study which combining the survey, interview, field observation, and documents review in the process of data collection method. Results show that in marketing attractiveness index, the market of cardiovascular healthcare system is attractive with score 61.5, meanwhile the competitive position of the Hospital XYZ is 59.8. The portfolio matrix which is implemented shows that offensive strategy is more suitable for the strategic marketing plan of the hospital for the upcoming years. There are two alternatives of offensive strategy which are ‘Growth Market Share’ strategy and ‘Expand Market Demand’ Strategy. Those strategies could be implemented by improving the quality of sales force, initiating the Corporate and Marketing Communication, and also expanding to B2B market by forcing Push and Pull Communication Strategy.